2018
DOI: 10.1159/000490016
|View full text |Cite|
|
Sign up to set email alerts
|

By Activating Akt/eNOS Bilobalide B Inhibits Autophagy and Promotes Angiogenesis Following Focal Cerebral Ischemia Reperfusion

Abstract: Background/Aims: Ischemic stroke is a leading cause of long-term disability. To date, there is no effective treatment for stroke. Previous studies have shown that Ginkgo biloba extract has protective effects against neurodegenerative disorders. In this present study, we sought to test the potential protective role of an active component of Ginkgo biloba extract, bilobalide, in a rat model of middle cerebral artery occlusion (MCAO). Methods: A rat model of MCAO was used to test the potential protective effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…In addition, BB was proved to function in declining inflammation, insulin resistance, and secretion of antigenic factors stimulated by hypoxia (Priyanka et al, ). Moreover, Zheng et al indicated that BB suppressed apoptosis, autophagy, and improved angiogenesis via AKT/endothelial nitric oxide synthase pathway (Zheng et al, ). BB was investigated to function in diverse cells and diseases, such as neural cell (Hua et al, ), SH‐SY5Y cells (Shi, Wu, Yew, Xu, & Zhu, ), gastric ulcer (Hui & Fangyu, ), and inflammatory pain (Goldie & Dolan, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BB was proved to function in declining inflammation, insulin resistance, and secretion of antigenic factors stimulated by hypoxia (Priyanka et al, ). Moreover, Zheng et al indicated that BB suppressed apoptosis, autophagy, and improved angiogenesis via AKT/endothelial nitric oxide synthase pathway (Zheng et al, ). BB was investigated to function in diverse cells and diseases, such as neural cell (Hua et al, ), SH‐SY5Y cells (Shi, Wu, Yew, Xu, & Zhu, ), gastric ulcer (Hui & Fangyu, ), and inflammatory pain (Goldie & Dolan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bilobalide, a component extracted from Ginkgo biloba extract, possess various kinds of properties. For example, bilobalide revealed neuroprotective effects in brain ischemic injury [6]; Bilobalide showed antioxidant potential in alleviating hypoxia-induced injury in 3T3-L1 adipocytes [7]; Bilobalide inhibited autophagy and promoted angiogenesis in cerebral ischemia-reperfusion [8]. Importantly, bilobalide demonstrated functions in the protection of the mitochondrial respiratory activity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We found that autophagy in cerebrovascular was downregulated in the 200 μg/mL group ( Figure 6K); however, in whole embryos, there was no change. Several studies have shown that decreased autophagy could inhibit pathways involved in angiogenesis 22 and autophagy triggered angiogenesis by activating VEGF and AKT. 23 Therefore, we hypothesised that the reduced autophagy level in cerebrovascular might contribute to cerebrovascular disappearance.…”
Section: Discussionmentioning
confidence: 99%